(untitled) (Eurasian Journal of Philology Science and Education, 2015)
In This article shows dramatical texts af actors estethetical character of using lingual – style. This article is considered the use of language in the speech of stylistic devices heroes of dramatic works. The article discusses the role of dialogue in dramatic works as well as a comprehensive study. In dramatic works and shows their nature and images of the characters. A study is also regarded Russian – Kazakh linguistics. In the article attaches importance using of actor’s stylistically literacy and dialogue, monologue, polylogue also dialecticism, barbarism of lexical elements. Only when the next conversation actor learned the culture of technics conversation on dramatic characters, and subordinate viewers. On stage, the actor tells the viewer down through the language of communication. Providence art word in a character deeply explores the scientific name of the lower classes flocks not only beautiful words, but in the future, should indicate.